Innovative Assessment of Crohn’s Disease: An Activity Prediction Tool Combining Laboratory Data and Imaging [Letter] - Wang F; Jiang Q; He P (Journal of Inflammation Research)
Fayuan Wang, Qinling Jiang, Ping He College of Integrated Traditional Chinese and Western Medicine, Southwest Medical University, Luzhou City, Sichuan Province, People’s Republic of ChinaCorrespondence: Ping He, College of Integrated Traditional Chinese and Western Medicine, Southwest Medical University, Luzhou City, Sichuan Province, 646000, People’s Republic of China, Email 1327255153@qq.com